Experimental study on static behavior of I-girder with concrete-filled rectangular flange and corrugated web under concentrated load at mid-span. (1st January 2017) - Shao, Yongbo; Wang, Yamin
Highlights: A new type of I-girder with concrete-filled tubular flange and corrugated web is presented. Experimental tests on both conventional plate I-girder and presented new I-girder are conducted. Failure process of both conventional and new I-girders is analyzed and discussed based on experimental results. Equations for predicting flexural strength of the new I-girders is presented. Abstract: This paper presented a new type of I-girder which consists of a rectangular concrete-filled tubular flange and corrugated web. In the new I-girder, the concrete-filled tubular flange has much stronger torsional and flexural stiffness, which is advantageous for improving the resistance to global buckling. Corrugated web, which is much lighter in weight due to its very small thickness compared to flat web with transverse or longitudinal stiffeners, has much better out-of-plane bending stiffness and shear stiffness, and thus it can enhance the capacity of resisting local buckling of the web more efficiently. To investigate the behavior of the presented new I-girder, experimental test is carried out to study the static failure process of a new I-girder specimen together with a corresponding conventional I-girder with flat-plate flanges and web. The two specimens are subjected to a concentrated load at the mid-span. Experimental results indicate that the failure of the traditional I-girder is global buckling while the presented new I-girder deforms gradually until a maximum deflection surpass the serviceability limit. It fails due to flexural yielding. The static performances of the two different I-girders, including strain development, lateral displacement development and load-deflection relationship, are compared and discussed in details based on the experimental results. Finally, theoretical equations for predicting the flexural strength of the new I-girder are presented, and the accuracy of these equations is also verified through comparison with experimental results.